Religious values and confidence in science: Perceived tensions and common ground - Isabelle Freiling; Michael A. Cacciatore; Meaghan McKasy (PLoS ONE, 2025)
While confidence in science is high compared to other institutions, many Americans question whether scientists share their values, including religious ones. Narratives surrounding science and religion often focus on a conflict between the two, but religious people, especially, tend to see their religious views as in line with science. Using survey data of two probability samples representative of U.S. adults, we examine how religious views, including perceptions of conflict and harmony between science and religion, predict confidence in science. We found that while general perceptions of religion and science as conflicting negatively predicted confidence in science, when individuals think religion endorses protecting the planet, their confidence in science was higher. The results suggest that attitudes toward religion and science are more nuanced than is often acknowledged and that audiences can be confident in science while holding strong religious beliefs. Further, the work suggests that finding and highlighting common ground between religion and science is a potentially promising avenue for cultivating confidence in science.